Pengaruh Pembentukan Peta Konsep Pada Materi Ikatan Kimia Bagi Siswa Kelas X Di SMA Negeri 1 Tondano - Ketty Preity Amelia Br Situngkir; freetje Waworuntu; Sonny Lumingkewas (Oxygenius: Journal Of Chemistry Education, 2023)
The purpose of this study was to determine student learning outcomes using the concept map formation strategy on chemical bonding material by comparing the average student learning outcomes of the experimental group using concept map formation and the control group using conventional methods. This research is an experimental study of two classes with a true experimental research design in the form of a posttest only control design. Samples were taken non-randomly, namely class X IPA 3 as the experimental class and X IPA 5 as the control class, with 30 students each. The average learning outcome of the experimental class is 87.12 and the average learning outcome of the control class is 81.84. Data for hypothesis testing is data obtained from posttest. Based on the one tailed hypothesis test at the significant level = 0.05, the value of tcount = 5.9967 and ttable of 2.001. The value of tcount> ttable, then H1 is accepted and H0 is rejected, this result shows that there is a difference in the average student learning outcomes from the experimental class and the control class, so it can be concluded that there is an effect of concept map formation on the average student learning outcomes in the chemical bonding material in class X. at SMA Negeri 1 Tondano.